Antiferromagnet-topological insulator heterostructure for polarization-controllable terahertz generation - Yu Cheng; Faran Zhou; Jing Teng; Peiyan Li; Litong Jiang; Piming Gong; Yongqing Li; Xiaojun Wu; Franz X. Kärtner; Jimin Zhao (Nature Communications)
Abstract Antiferromagnets (AFMs) are more advantageous in realizing ultrafast spin-based processes, but remain challenging to manipulate. The lack of proper knobs in AFM-based ultrafast devices greatly hampers their applications. Here, we innovate an antiferromagnet/topological insulator (AFM/TI) heterostructure MnSe/(Bi,Sb)2Te3 to realize laser-induced transient magnetic moment, and further demonstrate optically controllable circularly polarized ultrafast terahertz (THz) pulse generation, under zero external magnetic field. Intriguingly, we find two mechanisms underlying the ultrafast THz pulse generation: direct magnetic dipole radiation and spin-charge conversion resulted electric dipole radiation. Our findings provide a suitable platform for efficient and polarization-controllable ultrafast THz devices via optical means.